Are intertidal soft sediment assemblages affected by repeated oil spill events? A field-based experimental approach. (June 2016) - Sandrini-Neto, Leonardo; Martins, César C.; Lana, Paulo C.
Abstract: This study investigates the impact of repeated diesel spills on the structure of intertidal macrofaunal assemblages of a subtropical estuary. Three frequencies of exposure events were compared against two dosages of oil in a factorial experiment with asymmetrical controls. Hypotheses were tested to distinguish between (i) the overall effect of oil spills, (ii) the effect of diesel dosage via different exposure regimes, and (iii) the effect of time since last spill. Repeated oil spills dramatically altered the overall structure of assemblages and reduced the total density of macrofauna and densities of dominant taxa. Increasing the frequency of oil spills negatively affected macrofauna. In general, frequent low-dosage oil spills were more deleterious than infrequent high-dosage ones. However, increases in densities of some taxa, mainly the gastropod Heleobia australis, were observed in response to infrequent spills. Our results highlight the importance of repeated exposure events in determining the extent of oil impacts. Highlights: We experimentally assessed the impact of repeated diesel spills on macrofauna. Three frequencies of exposure events were contrasted against two dosages of oil. Assemblage structure was dramatically altered by frequent high-dosage spills. The main direct effect of diesel exposure was the decrease in species densities. In general, frequent small exposures were more deleterious than infrequent large ones. Abstract : We demonstrated that macrofaunal assemblages exposed to the same overall diesel release, but at distinct exposure regimes, are strongly affected by the frequency of oil spills.